Health Education for Diabetes Patients in Consumption of Oral Hypoglycemic Drugs (OHO) - Sylvia, Ester Inung; Munikaire, Ellen (Health Notions, 2018)
Diabetes mellitus is a disease of body metabolic disorders with a sign of an increase in blood glucose levels. This disease is chronic and requires treatment for life. The instability of blood glucose levels can cause chronic complications, so prevention is needed with treatment therapy. Compliance with someone taking oral hypoglycemic medication is one of the contributions to the occurrence or absence of complications of diabetes mellitus so education needs to be done so that the client is compliant in taking medication. This research was a quantitative type with the method of quasi experimental pre and post test without control. Subjects were respondents 34, selected by purposive  sampling. Data were analyzed by Wilcoxon test. The results showed that there was a significant difference between adherence to taking oral hypoglycemic drugs clients in Diabetes Melitus before and after health education with p-value of 0.000. Health education can support health programs in managing diabetes so as to produce changes and increase knowledge in controlling blood sugar levels in diabetes clients. Keywords: Health education, Diabetes mellitus, Oral hypoglycemic drug